Du rapport au savoir comme modalisation philosophique du savoir dans la philosophie pour enfants - Jean-François Goubet (Éducation et Socialisation)
Relation to knowledge is commonly used in the most diverse senses, for instance to refer to the social conditions of learning or to the psychological conditions of investment in school. The philosophical tradition has also the right to give a proper sense to relation to knowledge. Referring to distinctions coming from classical philosophy, in particular Plato and Kant, I want to take a personal look on philosophy for children (P4C). I shall base my paper on US examples given by Lipman or written down in the school curriculum of a German Land, the Mecklenburg-Vorpommern, in order to give more precisions about relation to knowledge. One of the major interests of P4C is that it introduces children to the complexity of their relation to the world: belief does not always yield to scientific knowledge, and knowledge can be understood in different ways, depending on the subject matter.